Business Going Concern: Encourage and Raise the Competitiveness of Small Businesses Through Digital Marketing Strategies - Juanim; Baihaqi, Muhammad Iqbal (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2025)
Small businesses face challenges in maintaining going concern, especially amid today’s disruptive era. An innovative digital marketing mix strategy is key to building competitive advantage and enhancing marketing performance. This study examines how small businesses adapt to complex environments. Findings show that a modern, technology-driven marketing mix significantly improves sustainable marketing performance. Among the four dimensions, digital-based promotion contributes the most. This study employs a descriptive quantitative approach with the aim of developing a comprehensive understanding of digital marketing strategies and their impact on sustainable marketing performance in small-scale hijab businesses. These results highlight that small businesses embracing digital innovation in their marketing strategies are more likely to sustain and compete effectively in the evolving market.